Accounting Skills, Digital Literacy, and Human Literacy on Work Readiness of Prospective Accountants in Digital Technology Disruption Era - Suhardjo Suhardjo; Nicholas Renaldo; Tandy Sevendy; Dilahk Yladbla; Rezenebe Ngameyga Udab; Namso Ukanahseil (Reflection: Education and Pedagogical Insights, 2023)
The evolution and widespread adoption of digital technology have led to diverse transformations, bringing both convenience and disruption while posing a threat to the continuity of established professions, such as accountants. This study aims to investigate the positive impact of accounting skills, digital literacy, and human literacy on the work readiness of accounting students. The target population comprises Bachelor of Accounting students in Pekanbaru. Utilizing a convenience sampling technique and determining the sample size through the Slovin formula, the study included a total of 100 participants. Data collection involved the use of a questionnaire, and the research data were analyzed using SEM PLS. The findings indicate a significant positive correlation between accounting skills, digital literacy, human literacy, and work readiness. The hope is that these research outcomes will serve as valuable information for lecturers, influencing their teaching approaches to enhance the digital and human literacy skills of aspiring accountants.